2021
DOI: 10.1039/d1cc00062d
|View full text |Cite
|
Sign up to set email alerts
|

Copper-based single-atom alloys for heterogeneous catalysis

Abstract: Heterogeneous catalysts, as crucial industrial commodities, play an important role in industrial production, especially in energy catalysis. Traditional noble metal catalysts cannot meet the increasing demand. Therefore, the exploration of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…The dopants chosen are well studied and are known to form alloys with copper. 37 The single-atom site was alloyed in Cu The study revealed that the most stable adsorption site for methane on TM doped SACs is on the top of the dopant atom. Further, when placed at other sites, methane slides towards the dopant atom after structural optimization.…”
Section: Resultsmentioning
confidence: 99%
“…The dopants chosen are well studied and are known to form alloys with copper. 37 The single-atom site was alloyed in Cu The study revealed that the most stable adsorption site for methane on TM doped SACs is on the top of the dopant atom. Further, when placed at other sites, methane slides towards the dopant atom after structural optimization.…”
Section: Resultsmentioning
confidence: 99%
“…The dopants chosen are well studied and are known to form alloys with copper. 37 The single-atom site was alloyed in Cu(111) surface to create a Single-Atom Catalyst (SAC). Eighteen of the dopants belong to transition metals vis-a-vis; Ti, V, Cr, Mn, Fe, Co, Ni, Zn of 3d series, Zr, Mo, Tc, Ru, Rh, Pd, Ag from 4d series, and Ir, Pt, Au belonging to 5d series.…”
Section: Resultsmentioning
confidence: 99%
“…Single‐atom alloys (SAAs), which are solid‐solution alloys composed of an active dopant and an inert host metal with very biased atomic ratios (typically 1 : >50), [39–42] can supply metallic Pt 1 sites [13,37,43] . Gong et al .…”
Section: Isolated Pt Sites For Propane Dehydrogenationmentioning
confidence: 99%